RRx-001: a chimeric triple action NLRP3 inhibitor, Nrf2 inducer, and nitric oxide superagonist - Oronsky, Bryan; Takahashi, Lori; Gordon, Richard; Cabrales, Pedro; Caroen, Scott; Reid, Tony (Frontiers in Oncology, 2023)
RRx-001 is a shape shifting small molecule with Fast Track designation for the prevention/amelioration of chemoradiation-induced severe oral mucositis (SOM) in newly diagnosed Head and Neck cancer. It has been intentionally developed or “engineered” as a chimeric single molecular entity that targets multiple redox-based mechanisms. Like an drug antibody conjugate (ADC), RRx-001 contains, at one end a “targeting” moiety, which binds to the NLRP3 inflammasome and inhibits it as well as Kelch-like ECH-associated protein 1 (KEAP1), the negative regulator of Nrf2, and, at the other end, a conformationally constrained, dinitro containing 4 membered ring, which fragments under conditions of hypoxia and reduction to release therapeutically active metabolites i.e., the payload. This “payload”, which is delivered specifically to hypoperfused and inflamed areas, includes nitric oxide, nitric oxide related species and carbon-centered radicals. As observed with ADCs, RRx-001 contains a backbone amide “linker” attached to a binding site, which correlates with the Fab region of an antibody, and to the dinitroazetidine payload, which is microenvironmentally activated. However, unlike ADCs, whose large size impacts their pharmacokinetic properties, RRx-001 is a nonpolar small molecule that easily crosses cell membranes and the blood brain barrier (BBB) and distributes systemically. This short review is organized around the de novo design and in vivo pro-oxidant/pro-inflammatory and antioxidant/anti-inflammatory activity of RRx-001, which, in turn, depends on the reduced to oxidized glutathione ratio and the oxygenation status of tissues.